FROM THE MEMORIES OF THE SCHOOL OF VITICULTURE AND ENOLOGY OF BENTO GONÇALVES/RS: DIALOGUES BASED ON NEWSPAPERS (1940–1959) (Interdisciplinary Studies Journal, 2025)
The present work aims to understand the genesis of the School of Viticulture and Enology of Bento Gonçalves through the analysis of local newspapers and the context of the viticulture and winemaking industry in the Serra Gaúcha during the period. The School of Viticulture and Enology, now the Bento Gonçalves Campus of IFRS, was established by Law No. 3,646, on October 22, 1959, with the purpose of training Technicians in Viticulture and Enology to meet the demand arising from the increasing complexity of the wine industry, which required the education of qualified professionals to work in this rapidly growing sector. Until that time, there was no formal training in enology in Brazil. This work falls within the field of the History of Education, with intersections in Professional Education and agricultural teaching. The methodology employed is historical document analysis based on the perspectives of Capelato (1988), De Luca (2018), and Barros (2023). The theoretical framework of the study is anchored in the concepts of Magalhães (2004), Koller and Sobral (2010), as well as studies on the history of grape growing and winemaking in the region. The period defined for the study includes the founding of the Experimental Enology Station of Bento Gonçalves, which can be considered the genesis of the school institution.
Keywords: School of Viticulture and Enology; Agricultural Policy; Authentic Texts; Technical and Vocational Education